Effects of Plant Growth-Promoting Rhizobacteria and Trichoderma sp. on Potato Growth on Medium Plains - Purwantisari, Susiana; Ferniah, Rejeki Siti; Nurchayati, Yulita; Jannah, Siti Nur (KnE Life Sciences, 2022)
The potato is a horticultural commodity with a high economic value and a consistent selling price. Indonesian potato production, however, remains lower than that of other Asian countries. One reason for this is that environmental sustainability has influenced the expansion of potato cultivation on a plateau, so medium plains have become an alternative. Aside from high-quality seeds, using plant growth-promoting rhizobacteria (PGPR) and Trichoderma sp. as an organic fertilizer is a strategic effort to boost potato yields on medium plains. The focus of this research was to examine how PGPR and Trichoderma sp. affect the growth of potatoes on medium plains. This study was carried out in Temanggung and Sawangan, Magelang, Jawa Tengah, at an altitude of 480 m.a.s.l, using the a complete random design with four different treatments: P0 = control, Treatment P1 = PGPR 20 ml/10 liter water, Treatment P2 = PGPR 40 ml/10 liter water, Treatment P3 = Trichoderma 80 gram/10 liter water, Treatment P4 = Trichoderma 150 gram/10 liter water, and Treatment P5 = PGPR 20 ml/10 liter water + Trichoderma 80 gram/10 liter water. The study found that a combination of PGPR and Trichoderma sp. treatment resulted in better growth than a single PGPR treatment. Keywords: biopesticide, organic fertilizer, PGPR